Recurrent hepatocellular carcinoma after liver transplant: identifying the high-risk patient - Nissen, Nicholas N (Blackwell Publishing Ltd, 2011)
BACKGROUND: Recurrence of hepatocellular carcinoma (HCC) after liver transplantation (LT) is rarely curable. However, in view of the advent of new treatments, it is critical that patients at high risk for recurrence are identified. METHODS: Patients undergoing LT for HCC at a single centre between 2002 and 2010 were reviewed and data on clinical parameters and explant pathology were analysed to determine factors associated with HCC recurrence. All necrotic and viable tumour nodules were included in explant staging. All patients underwent LT according to the United Network for Organ Sharing (UNOS) Model for End-stage Liver Disease (MELD) tumour exception policies. RESULTS: Liver transplantation was performed in 122 patients with HCC during this period. Rates of recurrence-free survival in the entire cohort at 1 year and 3 years were 95% and 89%, respectively. Thirteen patients developed HCC recurrence at a median of 14 months post-LT. In univariate analysis the factors associated with HCC recurrence were bilobar tumours, vascular invasion, and stage exceeding either Milan or University of California San Francisco (UCSF) Criteria. Multivariate analysis showed pathology outside UCSF Criteria was the major predictor of recurrence; when pathology outside UCSF Criteria was found in combination with vascular invasion, the predicted 3-year recurrence-free survival was only 26%. CONCLUSIONS: Explant pathology can be used to predict the risk for recurrent HCC after LT, which may allow for improved adjuvant and management strategies.